The Role of Microbiome in Human Health: Unveiling New Therapeutic Strategies in Disease Prevention and Treatment - Abdul-Jaleel, Safa Abbas; Awda, Zahraa Emad; Mahdy, Balqies Tahseen; Majed, Ali Laftah; Fares, Aisha Mezher (American Journal of Biology and Natural Sciences, 2025)
The human microbiome, a complex ecosystem of microorganisms residing in the body, plays a critical role in health and disease. Despite advancements in microbiome research, significant knowledge gaps remain regarding its mechanistic influence on metabolic and immune functions. This study employs metagenomic sequencing and computational analysis to examine microbiome diversity and its implications for disease prevention and treatment. Findings reveal that gut microbiota composition significantly affects metabolic regulation, immune response, and disease susceptibility. The results suggest that microbiome-targeted therapies, such as probiotics and fecal microbiota transplantation, offer promising strategies for managing chronic diseases. These insights underscore the need for personalized medicine approaches integrating microbiome data to enhance therapeutic interventions.